Mysteries of Type I IFN response: benefits versus detriments - Herbert Patrick Ludewick (Frontiers Research Topics, 2015)
Successful containment of an infection is dependent on both innate and adaptive immune response. Cytokines are essential effectors of both of these systems. In particular, type I interferons (IFN-I) are important components of early innate immunity against an infection. However, the production of IFN-I could serve as a double edge sword, either containing an infection or enhancing susceptibility. For example, IFN-I, which is essential for early containment of viral infections, has been shown to be detrimental to the host during bacterial infections. In fact, recent significant reports have shown that influenza virus induced IFN-I responses can enhance the host susceptibility to secondary bacterial infections. These recent reports highlight the expanding immunoregulatory role of IFN-I in the host immunity. With these recent findings in mind, the aim of this research topic is to welcome novel data, opinion and literature reviews on the newly identified dual functions of IFN-I. This research topic wills focus on the following areas of IFN-I: 1) a detrimental role of IFN-I during primary bacterial infection; 2) a detrimental role of viral infection induced IFN-I during secondary bacterial infections; 3) evolutionary pressure that drove detrimental IFN-I response during primary bacterial infection; and 4) does benefit of IFN-I responses during primary viral infections outweigh the adverse consequences of IFN-I mediated enhanced susceptibility to secondary bacterial infections.